Pemeriksaan Hemoglobidan Edukasi Anemia Dengan endekatan Komplementer Pada Remaja Putri - Qomariah, Siti; Darmadi, Darmadi; Juwita, Sellia; Saniya, Saniya; Donalizarti, Donalizarti (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2024)
Anemia is a nutritional problem throughout the world, especially in developing countries, including Indonesia. According to WHO, the prevalence of anemia in women in Indonesia is 23.9%, divided between the prevalence of anemia in women aged 5 to 14 years which is 26.4% and the prevalence of anemia in women aged 15 to 25 years which is 18.4%. Based on the results of Riskesdas in 2018, it was recorded that 26.8% of children aged 5-14 years suffered from anemia and 32% aged 15-24 years. Adolescent girls are 10 times more likely to suffer from anemia than teenagers. This community service is providing education and counseling regarding anemia to young women using a complementary approach at SMAN 7 Pekanbaru so that young women are related to anemia using a complementary approach. In this community service, Phase I Preparation is Anemia Education, Phase II Implementation is HB Examination and Phase III Evaluation is Evaluation of Anemia in Adolescents.  From the results of the HB examination of 137 teenage girls at SMAN 7 Pekanbaru, there were 7 teenage girls with mild anemia, while 137 were still in the normal category. There is still a lack of information regarding anemia in teenagers and examination results still show that young women have anemia.ABSTRAKAnemia adalah suatu masalah gangguan gizi di seluruh dunia, terutama di negara-negara berkembang, termasuk Indonesia. Menurut WHO, prevalensi anemia pada perempuan di Indonesia sebesar 23,9%, terbagi antara prevalensi anemia pada perempuan usia 5 sampai 14 tahun sebesar 26,4% dan prevalensi anemia pada perempuan usia 15 hingga 25 tahun yaitu 18,4%. Berdasarkan hasil Riskesdas pada tahun 2018, tercatat sebesar 26,8% anak usia 5-14 tahun menderita anemia dan 32% pada usia 15-24 tahun. Remaja perempuan 10 kali lebih mungkin mengalami menderita anemia dibandingkan remaja. Pengabdian kepada masyarakat ini adalah Memberikan Edukasi dan penyuluhan terkait Anemia pada remaja puteri dengan pendekatan komplementer di SMAN 7 Pekanbaru sehingga remaja puteri terkait Anemia dengan pendekatan komplementer. Dalam pengabdian masyarakat ini Tahap I Persiapan yaitu Edukasi Anemia, Tahapan II Pelaksanaan yaitu Pemeriksaan HB dan Tahap III Evaluasi yaitu Evaluasi tentang Anemia pada Remaja.  Dari hasil pemeriksaan  HB terhadap 137 remaja puteri SMAN 7 Pekanbaru terdapat 7 remaja puteri dengan anemia ringan, sedangkan 130 orang masih dalam kategori normal. Masih kurangnya informasi terkait anemia pada remaja dan hasil pemeriksaan masih ada menunjukkan remaja puteri mengalami anemia.